Neuroprotection as a Therapeutic Target for Diabetic Retinopathy - Cristina Hernández; Massimo Dal Monte; Rafael Simó; Giovanni Casini (Journal of Diabetes Research)
Diabetic retinopathy (DR) is a multifactorial progressive disease of the retina and a leading cause of vision loss. DR has long been regarded as a vascular disorder, although neuronal death and visual impairment appear before vascular lesions, suggesting an important role played by neurodegeneration in DR and the appropriateness of neuroprotective strategies. Upregulation of vascular endothelial growth factor (VEGF), the main target of current therapies, is likely to be one of the first responses to retinal hyperglycemic stress and VEGF may represent an important survival factor in early phases of DR. Of central importance for clinical trials is the detection of retinal neurodegeneration in the clinical setting, and spectral domain optical coherence tomography seems the most indicated technique. Many substances have been tested in animal studies for their neuroprotective properties and for possible use in humans. Perhaps, the most intriguing perspective is the use of endogenous neuroprotective substances or nutraceuticals. Together, the data point to the central role of neurodegeneration in the pathogenesis of DR and indicate neuroprotection as an effective strategy for treating this disease. However, clinical trials to determine not only the effectiveness and safety but also the compliance of a noninvasive route of drug administration are needed.